Gasoline: Influence of fuel-oxygen on NOx-emissions - Wensing, Michael; Münch, Kai-Uwe; Leipertz, Alfred; et al. (SAE Technical Papers, 1998)
Nitric oxides are the key pollutants emitted from SI engines today. In the work presented, the effect of different fuel-components on the NO x-emission of a four stroke SI engine and cross connections between different fuel properties were investigated in front of and behind the catalyst and compared to investigations described in literature. For the investigation presented a variety of different fuels has been produced. The content of aromatics, olefins, oxygen and the mid-range volatility has been changed systematically while only fuels with a good driveability were included in the investigation. The NOx-emission of 17 fuels tested was measured in front of and behind the catalyst. The tests were carried out with a single cylinder test engine using a constant air/fuel ratio. A special evaluation procedure was used, able to isolate the effect of each fuel component on the NOx-emission and the second order influence of each component on the effect of the other components from the experimental results. The measurements of the raw emissions in front of the catalyst confirm results already published. Fuels with a decreased content of the aromatic compounds and olefins as well as a decrease in the mid-range volatility lead to a reduction in the NO x-emissions while the effect of the aromatics content was about 3 times the effect of the other properties. An increase in the content of fuel oxygen was found to have a positive effect on raw NOx-emissions. In front of the catalyst no significant second order influence (effect one fuel property has got on the effects of other fuel properties) in between two of the properties varied was measured. Behind the catalyst it was found that fuel-oxygen is a keycomponent with a strong influence on the effect of other fuel components. A high content of oxygen lowers the effect of aromatics, olefins and evaporation properties on NOx-emission. For some fuel properties even the direction of the influence is changed by a different amount of fuel-oxygen. The second order influence of other fuel properties was found to be much lower compared to the influence of fuel-oxygen. © 1998 Society of Automotive Engineers, Inc.
Created from Fastlane, Scopus look-up